2018
DOI: 10.2460/javma.252.5.565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tramadol for treatment of osteoarthritis in geriatric cats

Abstract: OBJECTIVE To evaluate tramadol for treatment of signs of pain and impaired mobility in geriatric cats with osteoarthritis. DESIGN Randomized controlled crossover trial. ANIMALS 24 client-owned geriatric (≥ 10 years old) cats with osteoarthritis. PROCEDURES Otherwise healthy cats with owner-identified mobility impairment and clinical and radiographic evidence of osteoarthritis involving at least 1 appendicular joint were enrolled in the study. Cats were treated with tramadol orally at dosages of 0 (placebo), 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 39 publications
0
44
1
Order By: Relevance
“…It is known that nearly 20% of canine pets spontaneously develop osteoarthritis, and this translates to at least 15 million dogs in the USA alone [6]. OA mostly affects the large breed dogs [9], geriatric cats [10], and sport horses [11]. OA occurs in the dog populations mostly because of overweight and/or obesity, insufficient exercise, injury, becoming old, having an infection, immune disorders, or genetic predisposition [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that nearly 20% of canine pets spontaneously develop osteoarthritis, and this translates to at least 15 million dogs in the USA alone [6]. OA mostly affects the large breed dogs [9], geriatric cats [10], and sport horses [11]. OA occurs in the dog populations mostly because of overweight and/or obesity, insufficient exercise, injury, becoming old, having an infection, immune disorders, or genetic predisposition [12].…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, the only reported use of PRP in cats is that of a canine sourced PRP applied to a cutaneous wound of a feline patient (35). Prior work has shown promise using meloxicam, tramadol, and recently a feline-specific anti-nerve growth factor monoclonal antibody in cats with osteoarthritis (36)(37)(38)(39)(40). However, these medical options may be limited in some feline patients.…”
Section: Introductionmentioning
confidence: 99%
“…Non-steroidal antiinflammatory drugs are often contraindicated in geriatric cats with osteoarthritis due to concurrent chronic kidney disease. Some cats may develop dose-dependent side effects of tramadol use (36). Therefore, use of a feline sourced PRP may be particularly beneficial for patients with osteoarthritis and soft tissue injuries.…”
Section: Introductionmentioning
confidence: 99%
“…There are no approved medications for the treatment of chronic musculoskeletal pain in cats, and only a limited number of analgesic therapeutics with data about efficacy . Before the studies reported here, we surveyed veterinarians regarding pharmaceuticals and dietary supplements used for the alleviation of chronic pain in the cat .…”
Section: Introductionmentioning
confidence: 99%